SUN-LB90 Taurine Reverses Protein Malnutrition-Induced Endothelial Dysfunction of Pancreatic Vasculature - Guizoni, Daniele Mendes (J Endocr Soc, 2020)
Background: Pancreatic islets are highly vascularized and there is a correlation between endocrine pancreas function and pancreas perfusion. Protein malnutrition during early stages of development predispose to cardiovascular diseases, impaired insulin secretion and, type 2 diabetes. However, it is unknown if there are alterations in the pancreatic vasculature in response to malnutrition. Taurine (TAU) supplementation has been suggested as antihypertensive and improves endothelial function and insulin secretion in cardiometabolic disorders. Here, we investigated the effect of TAU in the vasorelaxation and endothelium-derived factors of the lieno-pancreatic artery from protein malnourished mice. Because lieno-pancreatic artery provides blood supply to pancreatic splenic lobe, a protective effect of TAU may result in cardiometabolic benefits. Methods: Post-weaned male C57Bl/6 mice fed a normal- (14%, NP) or a low-protein (6%, LP) diet for 90 days. Concomitantly, half of LP mice received 2.5% TAU in drinking water. Lieno-pancreatic artery (internal diameter ~ 160 µm) was isolated and concentration-response relaxation curves to acetylcholine (ACh), nitric oxide (NO)-donor (SNP), or hydrogen sulfide (H(2)S)-donor (NaHS) were performed. The involvement of NO and endothelium-derived hyperpolarization (EDH) in ACh-induced relaxation was assessed using L-NAME (NO synthase inhibitor) or KCl (to attenuate K(+) efflux), respectively. Protein expression was evaluated by Western-blot; NO and H(2)S production by DAF-2A and WSP-1 fluorescence, respectively. Results: Endothelium-dependent relaxation to ACh was reduced in lieno-pancreatic artery from LP compared with NP group. Either KCl or L-NAME reduced ACh-induced relaxation, but only KCl abolished differences between LP and NP, suggesting that EDH rather than NO is involved in the impaired endothelium-dependent relaxation of LP. In accordance, relaxation to SNP, NO production, and endothelial NO synthase (eNOS) expression were not altered in lieno-pancreatic artery of LP group compared to NP. Because H(2)S has been demonstrated to have EDH activity in several blood vessels we investigated this pathway. H(2)S production and NaHS-induced relaxation were both reduced in lieno-pancreatic artery of LP group compared with NP. TAU treatment reversed the impaired relaxation to ACh and to NaHS, as well as significantly increased H(2)S production in lieno-pancreatic artery of LP group. Conclusion: Protein malnutrition resulted in endothelial dysfunction of lieno-pancreatic artery associated with an impaired production and relaxation to H(2)S, which was restored by TAU. Therefore, beneficial effects of TAU on lieno-pancreatic artery vasodilatory function may result in improved pancreatic islet blood flow highlighting the potential of TAU for vasculo-metabolic protection.Funding: FAPESP, CAPES.